A Modified Thermal Model of Internal Grinding - Chang, Zhou; Hu, Lai (Manufacturing Technology Journal, 2022)
In the present study, an innovative method is proposed to improve the accuracy of thermal models of the grinding process. To this end, a set of orthogonal experiments are carried out to calculate heat flux using infrared temperature measurements. Then the convective heat transfer coefficient is modified based on the heat transfer and hydrodynamics theories. Finally, the modified heat flux and convective heat transfer coefficient are applied and a thermal model is established using ANSYS software. To verify the accuracy of the proposed model, a finite element grinding residual stress model based on the grinding heat and grinding force is established. By measuring the grinding residual stress and comparing it with the finite element residual stress model, the effectiveness of the grinding thermal model is indirectly verified. The obtained results demonstrate that the modified grinding thermal models are accurate and can be applied in engineering applications.
Keywords: Convective heat transfer; Heat distribution ratio; Grinding heat; Residual stress; Finite element method